Structural disorder and modular organization in Paramyxovirinae N and P - Karlin, David; Ferron, François; Canard, Bruno; Longhi, Sonia (Journal of General Virology, 2003)
The existence and extent of disorder within the replicative complex (N, P and the polymerase, L) of Paramyxovirinae were investigated, drawing on the discovery that the N-terminal moiety of the phosphoprotein (P) and the C-terminal moiety of the nucleoprotein (N) of measles virus are intrinsically unstructured. We show that intrinsic disorder is a widespread property within Paramyxovirinae N and P, using a combination of different computational approaches relying on different physico-chemical concepts. Notably, experimental support that has often gone unnoticed for most of the predictions has been found in the literature. Identification of disordered regions allows the unveiling of a common organization in all Paramyxovirinae P, which are composed of six modules defined on the basis of structure or sequence conservation. The possible functional significance of intrinsic disorder is discussed in the light of experimental data, which show that unstructured regions of P and N are involved in numerous interactions with several protein and protein–RNA partners. This study provides a contribution to the rather poorly investigated field of intrinsically disordered proteins and helps in targeting protein domains for structural studies.